Epidemiology, Phylogeny, and Evolution of Emerging Enteric Picobirnaviruses of Animal Origin and Their Relationship to Human Strains - Malik, Yashpal S. (Hindawi Publishing Corporation, 2014)
Picobirnavirus (PBV) which has been included in the list of viruses causing enteric infection in animals is highly versatile because of its broad host range and genetic diversity. PBVs are among the most recent and emerging small, nonenveloped viruses with a bisegmented double-stranded RNA genome, classified under a new family “Picobirnaviridae.” PBVs have also been detected from respiratory tract of pigs, but needs further close investigation for their inhabitant behavior. Though, accretion of genomic data of PBVs from different mammalian species resolved some of the ambiguity, quite a few questions and hypotheses regarding pathogenesis, persistence location, and evolution of PBVs remain unreciprocated. Evolutionary analysis reveals association of PBVs with partitiviruses especially fungi partitiviruses. Although, PBVs may have an ambiguous clinical implication, they do pose a potential public health concern in humans and control of PBVs mainly relies on nonvaccinal approach. Based upon the published data, from 1988 to date, generated from animal PBVs across the globe, this review provides information and discussion with respect to genetic analysis as well as evolution of PBVs of animal origin in relation to human strains.